ANALISIS BERPIKIR KREATIF SISWA DALAM MEMECAHKAN MASALAH PERSAMAAN KUADRAT BERDASARKAN GAYA KOGNITIF - Krisdiana, Ika; Lusiana, Restu; Sari, Dewi Kartika (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
In the standard contents of the 2013 curriculum it is mentioned that mathematics learning needs to be given at secondary school level, among others is to equip learners with the ability to think logically, critically, analytically, creatively, thoroughly and thoroughly, responsible, responsive, and not easily give up in solving problems. Especially creative thinking, it is necessary for students to build new ideas or ideas. This study aims to describe how creative thinking of vocational students in solving the problem of quadratic equations based on students' cognitive style. This research uses qualitative approach with descriptive type. Subjects in this study were students of class X SMKN 1 Jenangan Ponorogo district a number of 4 students. Researchers use triangulation method to test the validity of data. Data analysis techniques include 3 stages, namely data reduction, data exposure (data display), and conclusion drawing / verifying (conclusion drawing / verifying). The results showed that: 1) Students with cognitive style Field Independent in solving the problem meet the creative criteria with good category. 2) Students with cognitive style of Field Dependent in solving the problem meet creative criteria with category less up to well.